THE USE OF HYALURONIC ACID FOR CORRECTING FACE DEFORMITIES - Dias Machado, Daniel (Health and Society, 2023)
The use of injectable hyaluronic acid (HA) fillers has become increasingly widespread in facial contouring and rejuvenation. We report our experiences to emphasize the role of HA fillers as tools in addition to aesthetic treatments in cases of post-surgical facial sequelae. HA fillers are generally used for aesthetic rejuvenation, but a new potential horizon could be their application in traumatic, reconstructive and craniofacial surgeries. This study was carried out retrospectively through a bibliographic survey of books, public health manuals and scientific articles in Portuguese and English published in the databases of VHL (Virtual Health Library), SciELO (Scientific Electronic Library Online) and PUBMED. The search for references was developed by looking for publications referring to the period of the last 10 years. Visual analogue scale (VAS) assessment was performed to assess patient satisfaction. No major complications (ie impending necrosis or visual loss) were reported. Bruising and swelling have been reported for 48 hours after lip injection. In the immediate VAS assessment, 67% of the patients were “extremely satisfied” and 33% “satisfied”. In those 33%, VAS scores changed to “extremely satisfied” at 6–9 weeks and 3–6 months of VAS assessment (contextually for improvement in flexibility, elasticity, and aesthetic appearance of the tissue). The results indicate that this minimally invasive approach achieves a high level of aesthetic enhancement, improving patient satisfaction. The concept of HA filler applications may be a frontier that may be applicable to other areas of reconstructive facial plastic surgery.